Distance Work Changes Strategy of HR Management - M. V. Milenin (Plekhanov Russian University of Economics, 2020)
The development of new means of telecommunications, such as IP-telephony, messengers, applications for videoconferencing, platforms for distance work with documents (for example, googleapps) and others have been promoting recently the change-over of employees to distance (remote) work. The article analyzes findings of the survey dealing with distance work. Two hypotheses were put forward for the research: 1) work from home would be more productive for many people; 2) a lot of people would assess distance work positively and would prefer it to office work. Both hypotheses were confirmed by survey findings. Another goal of the research was to identify positive and negative sides of distance work with subsequent investigation of possibilities to eliminate minuses and of impact of pluses on employees’ motivation. Recommendations for companies’ executives and HR-divisions were prepared dealing with possibility and usefulness of full and partial change-over to remote work. In view of business, change-over of employees to distance work may have the following advantages: cut costs for rent of offices; upgrade business processes and communications; introduce advanced work technologies; raise efficiency, motivation and satisfaction of employees.